Performance evaluation of three yam storage structures in Fiaso in the Techiman Municipality, Ghana - Mwinibalonno, Mustapha Ghaniyu (2016)
A thesis submitted to The Department of Agricultural Engineering, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of degree in Master Of Philosophy (MPhil.) In Food and Postharvest Engineering, 2015